Pengaruh model talking stick berbantu media sudut jam terhadap kecerdasan intrapersonal siswa kelas IV di SDIT Al-uswah Kranggan - Redita Dwirani; Ari Suryawan; Kun Hisnan Hajron (Borobudur Educational Review, 2022)
This study aims to determine the effect of the talking stick learning model sudut jam (clock model) media on the Intrapersonal Intelligence of fourth grade students of SDIT Al-Uswah Kranggan, Temanggung Regency. It was a quantitative pre-experimental design type with one group pretest-posttest design. The subjects of this study were selected with saturated sampling technique. The samples in this study were fourth grade students of SDIT Al-Uswah Kranggan with a total of 12 students as the experimental class. The data collection method used was a pretest posttest questionnaire of students' intrapersonal intelligence. SPSS version 16.00 was used to know the results of the validation test, reliability test, normality test, and hypothesis test using. The validity test of the intrapersonal intelligence questionnaire used Pearson Correlation, and the reliability of instrument used Cronbach's Alpha. The data analysis technique in this study used the analysis prerequisite Shapiro-Wilk test and hypothesis testing used the Paired Sample t-test. The results of the parametric statistical test using the Paired Sample t-test showed that the significance value (2-tailed) was 0.000, which is < 0,05 means that the HO was rejected and Ha was accepted. Therefore it can be said that the talking stick learning model assisted with sudut jam (clock model) media has a significant effect on the intrapersonal intelligence of fourth grade students of SDIT Al-Uswah Kranggan Temanggung.